Education on Garden Land Utilization in Efforts to Prevent Stunting in Padang City - Rahmi Awalina; Yeffi Masnarivan; Resmiati Resmiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The issue of stunting is a global problem that has become the focus of the government's efforts to address it. Based on observations of the nutritional status of toddlers at Posyandu Harapan Ibu, 6 out of 149 toddlers, ten are experiencing stunting, accounting for approximately 6.71% of the total number of toddlers. An initial survey conducted by the community engagement team among ten mothers with toddlers in the Posyandu Harapan Ibu 6 area revealed that most (80%) of these mothers lack knowledge regarding stunting, its prevention, management, and associated risks. The Mata Air area in Padang City, which is part of Posyandu Harapan Ibu 6, has a relatively high prevalence of stunting. However, the potential of family backyard spaces in this area has yet to be optimally utilized. This community engagement initiative aims to enhance the use of family backyard spaces as a source of nutrition for families to prevent stunting. The method employed involves educating local volunteers about the benefits of family backyard spaces as an alternative source of family food, followed by the distribution of plant seeds and planting media. The results of the outreach activities indicate that (1) participants respond to the outreach activities with enthusiasm and vigor, (2) Participants actively engage and proactively participate in the outreach process, and (3) Participants have initiated the implementation of recommendations by utilizing family backyard spaces as a source of food and nutrition for their families by planting the provided plant seeds. This community engagement effort represents a positive endeavor to prevent stunting in the Mata Air area.